2022
DOI: 10.3390/life12071075
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Kefir on Epidermal Water Homeostasis in Healthy Human Skin

Abstract: Kefir, a symbiotic consortium of diverse bacteria and yeasts, is one of the most popular probiotic foods on the market. Its consumption has been referred to as beneficial in human skin health, namely in the reinforcement of skin’s barrier function. This benefit likely results from the productive activity of lactic acid bacteria during kefir fermentation. Lactic acid is naturally present in the skin, and actively contributes to epidermal water dynamics and “barrier.” Few studies have been conducted regarding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…In addition to the decreased TEWL, skin hydration was elevated after both 28 and 56 days of treatment (Figure 4). Ingestion of probiotics has also previously shown ability to decrease TEWL in the skin and increase the barrier function 16 . Mode‐of‐action has been determined as affecting transcriptional regulation and anti‐inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the decreased TEWL, skin hydration was elevated after both 28 and 56 days of treatment (Figure 4). Ingestion of probiotics has also previously shown ability to decrease TEWL in the skin and increase the barrier function 16 . Mode‐of‐action has been determined as affecting transcriptional regulation and anti‐inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…Ingestion of probiotics has also previously shown ability to decrease TEWL in the skin and increase the barrier function. 16 Mode-of-action has been determined as affecting transcriptional regulation and anti-inflammatory properties. Studies have found that ingestion of Bifidobacterium breve could alleviate photo-aging.…”
Section: Discussionmentioning
confidence: 99%
“…Existen diversos estudios que apuntan a que el consumo de kéfir de agua de manera regular tiene beneficios a la salud, entre los que se menciona la mejora en la apariencia de la piel [4]; por su carácter probiótico contribuye a facilitar la digestión y mejorar la flora intestinal. 5…”
Section: Introductionunclassified